1992
DOI: 10.1128/jb.174.14.4638-4646.1992
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the Entner-Doudoroff pathway in Escherichia coli: sequence analysis and localization of promoters for the edd-eda operon

Abstract: The nucleotide sequence of the entire Escherichia coli edd-eda region that encodes the enzymes of the Entner-Doudoroff pathway was determined. The edd structural gene begins 236 bases downstream ofzwf. The eda structural gene begins 34 bases downstream of edd. The edd reading frame is 1,809 bases long and encodes the 602-amino-acid, 64,446-Da protein 6-phosphogluconate dehydratase. The deduced primary amino acid sequences of the E. coli and Zymomonas mobilis dehydratase enzymes are highly conserved. The eda re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
74
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 39 publications
4
74
0
Order By: Relevance
“…The amino acid sequence predicted by the ORF exhibited 60% identity with and 76% similarity to the amino acid sequence of EDD from E. coli (21) and 55% identity with and 71% similarity to that of EDD from Z. mobilis (3) (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid sequence predicted by the ORF exhibited 60% identity with and 76% similarity to the amino acid sequence of EDD from E. coli (21) and 55% identity with and 71% similarity to that of EDD from Z. mobilis (3) (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Computer analysis of initial sequence data revealed an ORF extending from within the 247-bp fragment in pPZ196 whose predicted amino acid sequence exhibited a high degree of homology with the EDD sequences from E. coli (21) and Zymomonas mobilis (3). The complete edd sequence from P. aeruginosa consisted of 1,833 bp encoding a 610-amino-acid protein with a predicted molecular weight of 65,140 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the D-arabinonate dehydratase from S. solfataricus belongs to COG4948, the same function seems to be performed by members of COG0129 that are commonly annotated as dihydroxyacid dehydratases (IlvD) or 6-phosphogluconate dehydratases (Edd) (67). A member of this family has recently been characterized from S. solfataricus (DHAD, Sso3107), which revealed a broad substrate specificity for aldonic acids (68).…”
Section: Resultsmentioning
confidence: 99%
“…Although this reaction has not been shown to occur in vivo, cleavage of KHG could serve in tricarboxylic acid (TCA) cycle regulation or, when operating in the reverse direction, in the detoxification of glyoxylate. Cloning and sequencing the genes encoding these functions revealed that KHG aldolase and Eda are the same enzyme (7,18). However, this study is the first to extensively characterize eda regulation.…”
mentioning
confidence: 98%